The Influence of Internal Audit on the Quality of Financial Reports (Case Study at Mitra Guna Prima Company) - Gilbert Rely (SEAN Institute, 2023)
Internal audit is an evaluation process carried out systematically and independently to assess the effectiveness and efficiency of the management process and compliance with applicable policies and procedures. Good report quality is very important for managerial and stakeholder decision making. This study aims to analyze the effect of internal audit on report quality at Mitra Guna Prima Company. The method used in this study is a quantitative approach with data collection through questionnaires distributed to 96 respondents who are employees at Mitra Guna Prima Company. The collected data were analyzed using simple linear regression analysis to determine the relationship between internal audit variables and report quality. The results of the study indicate that there is a positive and significant effect between internal audit on report quality at Mitra Guna Prima Company, where increasing the effectiveness of internal audit is followed by an increase in the quality of the reports produced. These findings are expected to provide insight for Mitra Guna Prima Company management in improving the internal audit system to support transparency and accountability of company reports.